Association of mindfulness with female sexual dysfunction. (July 2022) - Sood, Richa; Kuhle, Carol L.; Thielen, Jacqueline M.; Kapoor, Ekta; Vencill, Jennifer A.; Mara, Kristin C.; Faubion, Stephanie S.
Highlights: Higher mindfulness was associated with lower odds of having sexual dysfunction. Higher mindfulness was associated with better scores for sexual function. Higher mindfulness correlated with lower sexual distress, controlling for scores on the female sexual function index. Higher mindfulness correlated with better scores in all subdomains of the female sexual function except pain. Abstract: Objectives: Female sexual dysfunction (FSD) affects women of all ages. It is often a multifactorial problem with a strong psychosocial component. Mindfulness may help alleviate FSD with nonjudgmental, present-moment awareness and decreased emotional reactivity. The goal of this study was to assess the association between dispositional or trait mindfulness and FSD. Study Design: In this cross-sectional study at a tertiary care women's health clinic, 1718 cisgender women (mean age, 51.9 years) completed the Mindfulness Attention Awareness Scale (MAAS), Female Sexual Function Index (FSFI), and Female Sexual Distress Scale–Revised (FSDS-R). Main Outcome Measures: Regression analysis was used to test the associations of mindfulness, sexual function, and sexual distress with univariate and multivariable analyses, adjusting for potential confounders. Results: Within the sample, 57% of women met FSD criteria (FSFI scores ≤26.55 and FSDS-R ≥ 11). On univariate analysis, higher MAAS scores, signifying greater mindfulness, were associated with higher (better) sexual function scores, lower sexual distress scores, and lower odds of FSD. This association persisted on multivariable analysis after adjusting for potential confounders. Conclusions: Higher trait mindfulness was associated with better sexual function, lower sexual distress, and lower likelihood of FSD. Further studies are needed to assess the role of mindfulness in mitigating FSD.